Pantang Larang Bermain Waktu Magrib (Kajian Living Hadis Tradisi Masyarakat Melayu Sambas) - Syamsul Kurniawan (Jurnal Living Hadis, 2019)
Frank Swettenham (2003) assumed Malays as followers of the Prophet Muhammad and believe in fate, but also believe in superstition. As abstinence forbidding children play at sunset, the base develops as a form of their belief in the existence of ghosts and demons. Abstinence for children playing at Magrib is a living hadith phenomenon because it relies on a hadith of the Prophet Muhammad: "Don't let your children leave at sunset until the darkness of the night disappears because the devil disperses if the sun goes down until the darkness of the night disappears”. Portrait of living hadith in abstinence from playing at sun set prayer (Magrib) is actually easy to understand given the flexible nature of Islam so that it is able to unite and merge with any culture, period or environment. The focus of this paper is the abstinence for children playing at sun set prayer time as the phenomenon of the living hadith that developed among the Sambas Malays.Abstrak Frank Swettenham (2003) mengasumsikan Masyarakat Melayu sebagai pengikut Nabi Muhammad Saw dan percaya takdir, namun juga memercayai takhayul. Sebagaimana pantang larang bermain di waktu Magrib, yang dasarnya berkembang sebagai bentuk kepercayaan mereka tentang keberadaan hantu dan setan. Pantang larang bagi anak-anak bermain di waktu Magrib ini merupakan fenomena living Hadis, karena bersandar pada sebuah Hadis Nabi Muhammad Saw: “Jangan kalian membiarkan anak anak kalian di saat matahari terbenam sampai menghilang kegelapan malam sebab setan berpencar jika matahari terbenam sampai menghilang kegelapan malam.” Potret living Hadis dalam pantang larang bermain di waktu Magrib ini, sesungguhnya mudah dimengerti mengingat watak agama Islam yang fleksibel, sehingga mampu menyatu dan melebur dengan budaya, masa maupun di lingkungan masyarakat manapun. Fokus tulisan ini adalah pantang larang bagi anak-anak bermain di waktu Magrib sebagai fenomena living Hadis yang berkembang di kalangan Masyarakat Melayu Sambas